Efektifitas Permainan Bola dan Rintangan untuk Stimulasi Perkembangan Motorik Kasar Anak Usia 4-6 Tahun - 'Aziz, Hafidh; Ajhuri, Kayyis Fithri; Humaida, Rifqi (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2021)
This study aims to determine the effectiveness of the combination game between ball and obstacles to stimulate gross motorik development of children aged 4-6 years. This research is quantitative research with a quasi-experimental design using single group pre-test and post-test types. The object of study is children aged 4-6 years at RA Riyadussalihin Moyudan Sleman, and the total population is 41 children who are then taken all as research samples. The data collection method is based on the results of the test observations before being given treatment and the post-test results after being given treatment. Based on the study results, it was found that there was an effect of the application of the combination game of ball and obstacle on the gross motorik development of children aged 4-6 years. As evidenced by the statistical test results, they were 0.001 for the aspect of throwing strength, 0.019 for the accuracy of catching the ball, and 0.000 for the agility aspect of overcoming obstacles. The statistical test results of the three factors are overall smaller than 0.05. It means that there are differences in the pre-test and post-test results. The ball and obstacles game affects children's gross motor development. This research contributes to understanding the effectiveness of ball and obstacle games for stimulating children's gross motor development. It can be a reference for learning programs and fostering children's motor development.